A versatile American institution: the changing ideals and realities of philanthropic foundations - Hammack, David C.; Anheier, Helmut K. (Brookings Institution Press, 2013)
"America's grantmaking foundations have grown rapidly over the course of recent decades, even in the face of financial and economic crises. Foundations have a great deal of freedom, enjoy widespread legitimacy, and wield considerable influence. In this book, David Hammack and Helmut Anheier follow up their edited volume, American Foundations, with a comprehensive historical account of what American foundations have done with that independence and power. While philanthropic foundations play important roles in other parts of the world, the U. S. sector stands out as exceptional. Nowhere else are they so numerous, prominent,or autonomous. What have been the main contributions of philanthropic foundations to American society? And what might the future hold for them?" --